Evaluation of volatile chlorinated hydrocarbons distribution along depth profiles in the Ross Sea, Antarctica - ZOCCOLILLO, Lelio; INSOGNA, SUSANNA; Carlo Abete; Claudia Cafaro (Microchemical Journal, 2009)
The presence and the distribution along depth profiles of volatile chlorinated hydrocarbons (VCHCs) were evaluated in seawater samples collected in the Ross Sea (Southern Ocean, Antarctica) during the 2002-2003 Italian expedition. Sampling areas were located where the Circumpolar Deep Water interacts with the shelf waters that supply the Ross Sea. The VCHCs investigated were: 1,1,1-trichloroethane (C(2)H(3)Cl(3)), tetrachloromethane (CCl(4)), trichloroethylene (C(2)HCl(3)). tetrachloroethylene (C(2)Cl(4)). The analytical procedure consisted of a liquid-liquid extraction carried out with n-hexane directly in Antarctica, followed by gas chromatographic analysis with electron capture detection carried out in Italy. Concentration levels for the VCHCs analysed ranged from digits to hundreds of ng/L according to the station, depth and substance considered. Important differences in concentration levels between the three stations near the Ross Ice Shelf and the two stations located in the Cape Adare area were observed. In particular the stations situated in the Cape Adare zone, at certain depths, showed a thermal inversion due to the mixing of the Circumpolar Deep Water with the waters generated inside the Ross Sea Basin. The lowest concentration levels were recorded at this temperature increase. (C) 2008 Elsevier B.V. All rights reserved.